Ketergantungan Teknologi: Analisis Perilaku Mahasiswa Dalam Penggunaan Gadget Dan Media Sosial Pada Mata Kuliah Pengelolaan Kelas Di Iain Ponorogo - Rosidatul Khasanah (https://ejournal.insuriponorogo.ac.id/, 2024)
The development of Information Communication Technology (ICT) has had a significant impact on the educational process, especially for Islamic Religious Education students at IAIN Ponorogo. The aim of this article is to find out how the use of ICT influences their learning. The research method used is qualitative, with a focus on interviews and observations of how students use gadgets and social media during the learning process. The research results show that students tend to rely on their gadgets to access information and interact with learning material. Uncontrolled use of gadgets can disrupt concentration and learning effectiveness, and can cause disruption in class. This article also underlines the importance of good technology ethics in the learning context, including awareness of the use of gadgets and social media and the ability to manage distractions that may arise. The role of lecturers in monitoring student activities to ensure appropriate and productive use of technology is also explained. By integrating research results with a literature review, this article provides insight into the impact of ICT use in learning and highlights the importance of using technology wisely. The hope is that this understanding can help students and lecturers make optimal use of ICT in the educational context.